Development and application of conceptual and analytic frameworks for community engagement at a South African higher education institution - Nkoana, E.M.; Dichaba, M.M. (South African Journal of Higher Education, 2017)
University-community engagement is gaining momentum as the latest core business of South African universities in addition to teaching and learning. However, the lack of conceptual and analytic frameworks to assess the progress towards realising university-community engagement will eventually invite criticism that might harm genuine university-community relations. This paper uses a systematic literature review approach to develop conceptual and analytic frameworks that are later applied to critically assess the university-community engagement of a leading South African university. Results show that the poor conceptualisation of university-community engagement affects its operationalisation leading to dominant ‘weak’ as opposed to ‘strong’ university-community engagement initiatives. Last, the environmental management field offers great opportunities for genuine UCE with community members.